The Influence of the Problem Based Learning Model on the Spatial Thinking Skills of High School Students in Geography Learning - Irwan Abdullah; Enok Maryani; Epon Ningrum; Iwan Setiawan (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
In geography instruction, classroom practices remain largely dominated by conventional, teacher-centered approaches, which limit students’ opportunities to develop analytical, evaluative, and contextual reasoning related to geosphere phenomena. This study aims to analyze and evaluate the effect of implementing the Problem-Based Learning (PBL) model on students’ spatial thinking skills in geography education. The study employed an experimental method with a nonequivalent control group design involving two groups: an experimental group and a control group. The research sample consisted of 30 students selected through purposive sampling. Data were collected using written essay-based test instruments administered as pre-tests and post-tests, designed to measure analytical ability, spatial reasoning, and spatially oriented problem-solving skills. Quantitative data analysis included tests of normality and homogeneity, hypothesis testing, correlation analysis, coefficient of determination, and n-gain analysis to assess the level of improvement and the effectiveness of the instructional model across both groups. The results indicate that the implementation of the PBL model significantly enhances, strengthens, and optimizes students’ spatial thinking skills compared to conventional instruction. Thus, PBL is proven to be more effective in fostering higher-order thinking skills among students. The findings suggest that PBL holds strategic potential for broader implementation and further development in secondary school geography instruction to strengthen spatial thinking as a key 21st-century competency.